Integrating Green Product Innovation and AI in Business Strategies for Competitive Advantage: A Study of Indonesian's Future - Ardiansyah, Eka (JURNAL BISNIS STRATEGI, 2025)
This study examines the integration of green product innovation and artificial intelligence (AI) within business strategies in Indonesia, aiming to identify how companies can leverage these elements for competitive advantage. Through a mixed-methods approach, combining qualitative interviews with industry experts and quantitative surveys of business practitioners, the research highlights the pressing need for sustainable practices amid Indonesia's unique environmental challenges. Findings indicate that a significant majority of businesses recognize the importance of green innovation and AI; however, there exists a notable gap in the effective implementation of AI strategies. Barriers, such as a lack of skilled labor and regulatory complexities, hinder progress. Despite these challenges, the integration of AI can enhance operational efficiencies, resource management, and the development of eco-friendly products, which align with consumer preferences for sustainability. The findings provide actionable insights for Indonesian firms seeking to harmonize green product innovation and AI, emphasizing the role of intellectual capital in facilitating this integration. Ultimately, this research contributes to a deeper understanding of how Indonesian businesses can maintain competitiveness while advancing sustainable practices essential for future market success.